2019
DOI: 10.1080/17482631.2018.1563429
|View full text |Cite
|
Sign up to set email alerts
|

Expanding knowledge and roles for authority and practice boundaries of Emergency Department nurses: a grounded theory study

Abstract: Purpose: While emergency department nurses in Indonesia are critical to quality care, the role lacks recognition and standard practices and regulation of scope of practice are absent. This research explored the role of nurses in Indonesian EDs. Method: The conceptual lens applied in the research was grounded theory. The main data source was 51 semi-structured interviews with 43 ED nurses, three directors of nursing, three nurse leaders and two nurse educators. Data were also generated through observations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Additionally, most of the emergency nurses still felt the importance of improving their knowledge and skills related to emergency nursing practice. 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, most of the emergency nurses still felt the importance of improving their knowledge and skills related to emergency nursing practice. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Research competencies 17 are important for improving the quality of emergency healthcare services to achieve the best possible clinical outcomes for patients in the ED. This competency is not only critical for emergency nurses but also for nursing as a profession because this research competency is linked to the development of emergency nursing knowledge and the ownership of knowledge for the profession.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses and auxiliary staff in our study reported significantly higher levels of burnout than physicians. This may be related to the continuous multitasking and heavy workload among nurses (Huhtala, 2021; Trisyani & Windsor, 2019), which might be a source of frustration and increase burnout. The demands and intensity of their work, together with the emotional burden of caring for mentally ill and the possibly excessive expectations of patients, may foster despair, nervousness, angry outbursts and a decline in sensitivity and empathy towards patients.…”
Section: Discussionmentioning
confidence: 99%
“…It creates an opportunity for other healthcare providers to look down on nurses. Several studies found that nurses feel dissatisfied with their autonomy ( Asmirajanti et al, 2019 ; Ibrahim, 2017 ; Trisyani & Windsor, 2019 ). Moreover, nurses have leadership barriers in the organization's structure and hierarchy, making them unable to speak up and become followers ( Wardani & Ryan, 2019 ).…”
Section: Discussionmentioning
confidence: 99%